Dukungan Orang Tua dengan Perilaku Cuci Tangan dan Gosok Gigi pada Anak di TK ABA Kepiton, Kulon Progo - Isman Susanto; Nita Fitriana (Alma Ata University Press, 2015)
Childhood is a time that very susceptible to various diseases due to a less of affective sanitation and poor hygiene. Hands washing and teeth brushing behavior are part of the health behaviors that need to be invested to prevent the diseases. Parents have important role in providing support and maintaining their children’s health care. Objective of this research was to know a relationship between parents support with hands washing and teeth brushing behaviors among children in Kindergarten ABA Kepiton, Kulon Progo. This research was a Quantitative inductive research with cross sectional study approach. The Population were all of children and parents of children attending in kindergarten ABA Kepiton, Kulon Progo which consisted of 37 childrens. With a total sampling method, the number of samples was meet inclusion and exclusion criteria were 35 childrens. Analysis of the data used Fisher’s Exact Test. Results of Fisher’s Exact Test showed that there was relationship between parents support and hands washing behavior in children, p-value =0.009 (p<0.05) and there was no relationship between parents support and teeth brushing behavior in children, p-value=0.292 (p>0.05). In conclusion, there was a relationship between parents support and hands washing behavior in children and there was no relationship between parents support and teeth brushing behavior in children.